Physoderinae Miller, 1954 (Hemiptera: Heteroptera: Reduviidae): a junior synonym of Epiroderinae Distant, 1904, and a junior homonym of Physoderina Chaudoir, 1877 (Coleoptera: Carabidae) - Rédei, Dávid (Zootaxa, 2017)
The purpose of the present paper is to review and resolve nomenclatural problems with the family-group name Physoderinae Miller, 1954 (type genus: Physoderes Westwood, 1846), a name being in prevailing usage for a subfamily of assassin bugs (Hemiptera: Heteroptera: Reduviidae). It is demonstrated that this name is a junior synonym of Epiroderinae Distant, 1904 (type genus: Epirodera Westwood, 1847, a junior objective synonym of Physoderes) and permanently invalid as a junior homonym of the family-group name Physoderina Chaudoir, 1877 (type genus: Physodera Eschscholtz, 1829) (Coleoptera: Carabidae: Harpalinae: Lebiini), therefore it is replaced by its senior synonym, Epiroderinae.